Quality of the ICD-11 Beta Draft from the German Perspective: Evaluation Based on the Alphabet of ICD-10-GM 2017 - Stausberg, Jürgen (Methods of Information in Medicine, 2018)
Objectives: The German Association for Medical Informatics, Biometry and Epidemiology implemented a field test for the ICD-11 Beta Draft. Aim was to analyze completeness and appropriateness of the ICD-11 Beta Draft in its entire breadth.Methods: Starting point was the synonym thesaurus (“Alphabet”) of the German modification of ICD-10. The Alphabet included a list of diagnoses terms that supports the coding of diagnoses with ICD-10. A sample of 60,328 diagnosis terms was drawn to be mapped to the ICD-11 Beta Draft. A subsample of 13,975 diagnosis terms was prepared for assessing reliability. First, the coders had to assign a diagnosis term from the sample to an appropriate English one. This included the automatic selection of the respective code from the ICD-11 Beta Draft. Secondly, the coders had to answer questions regarding completeness, appropriateness, and other issues.Results: Finally, 49,184 results from 36 coders were available for the analysis. Problems with completeness were indicated in 4.7% of the results, problems with appropriateness in 5.3%. On the level of chapters, Cohen’s kappa reached grade “fair” at a maximum. The coders agreed in 31.4% of the terms.Conclusions: Problems with the ICD-11 Beta Draft appeared to be moderate. Completeness was high, reliability was low as it is known for ICD-10. Concerns with the structure of the ICD-11 Beta Draft were noted, e. g. for neoplasms. A post processing of the ICD-11 Beta Draft seems to be sufficient with regard to the content. Methodologically, a thorough review of the structure might be advisable.
Keywords: Classification; coding; diagnoses; International Classification of Diseases; reliability